2011
DOI: 10.1016/j.jcp.2011.03.030
|View full text |Cite
|
Sign up to set email alerts
|

Time domain numerical modeling of wave propagation in 2D heterogeneous porous media

Abstract: This paper deals with the numerical modeling of wave propagation in porous media described by Biot's theory. The viscous efforts between the fluid and the elastic skeleton are assumed to be a linear function of the relative velocity, which is valid in the low-frequency range. The coexistence of propagating fast compressional wave and shear wave, and of a diffusive slow compressional wave, makes numerical modeling tricky. To avoid restrictions on the time step, the Biot's system is splitted into two parts: the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
54
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(55 citation statements)
references
References 48 publications
(96 reference statements)
0
54
0
1
Order By: Relevance
“…We have no theoretical estimate of RðSÞ, but numerical studies have shown that this value is similar to that of the spectral radius in LF: ðg=jÞðq=vÞ, which can be very large. 6 The time step can therefore be highly penalized in this case [Eq. (40)].…”
Section: A Splittingmentioning
confidence: 99%
See 1 more Smart Citation
“…We have no theoretical estimate of RðSÞ, but numerical studies have shown that this value is similar to that of the spectral radius in LF: ðg=jÞðq=vÞ, which can be very large. 6 The time step can therefore be highly penalized in this case [Eq. (40)].…”
Section: A Splittingmentioning
confidence: 99%
“…5 and the introduction to Ref. 6 for general reviews. In the HF regime, the fractional derivatives greatly complicate the numerical modeling of the Biot-JKD equations.…”
Section: Introductionmentioning
confidence: 99%
“…Appendix B. Scattering of a plane wave at oblique incidence on a plane homogenized interface We consider a plane wave at oblique incidence θ on the thick interface and the problem to solve is (5). We want to determine u(x, y, ω) in (42), and u is defined in (7). Below, we shall calculate the pressure p afterwards u = (v x , v y , p) T is deduced using (5) written in the harmonic regime, with time dependence e −iωt , whence…”
Section: Resultsmentioning
confidence: 99%
“…Let us begin with the classical case of acoustics where the jump conditions do not involve spatial derivatives: for instance, v n = 0 and p = 0. In this case, taking k = r maintains a r-th order global accuracy [7] (the criterion k = r − 1 is even sufficient [8]). In the non-classical case studied here, the jump conditions involve first-order spatial derivatives.…”
Section: High-order Compatibility Condition Eq (12)mentioning
confidence: 99%
“…The purpose of this paper is to simulate wave propagation for transverse porous media. For the LF-Biot equations, we use the direct method to handle the viscous term, which is different from the splitting method [16,26,13]; both the single material and heterogeneous materials with point source tests are considered. For the Biot-JKD equations, we applied the technique developed in [35] for dealing with the memory term and solve the augmented Biot-JKD equations, which deal with the memory terms by using auxiliary variables derived from the JKD-tortuosity.…”
Section: Introductionmentioning
confidence: 99%